Inhibitory Effects of Maleimide Derivatives from the Mycelia of the Fungus Antrodia cinnamomea BCRC 36799 on Nitric Oxide Production in Lipopolysaccharide (LPS)‐Activated RAW264.7 Macrophages. Issue 3 (13th March 2013) - Wu, Ming‐Der; Cheng, Ming‐Jen; Yech, Yi‐Jen; Yuan, Gwo‐Fang; Chen, Jih‐Jung
Abstract Four new maleimide derivatives, antrocinnamomins E–H (1–4, resp.), together with (3S, 4R)‐1‐hydroxy‐3‐(4‐hydroxyphenyl)‐4‐(2‐methylpropyl)pyrrolidine‐2, 5‐dione (5) and ergosterol were isolated from the mycelia of Antrodia cinnamomea BCRC 36799. The structures were elucidated by 1D‐ and 2D‐NMR spectroscopy, and mass spectrometry. Compounds 1–5 were evaluated for their inhibitory effects on nitric oxide (NO) production by macrophages. Compounds 2 and 4 showed stronger inhibition of NO production than the positive control quercetin.